Prevalence and Associated Factors of Alexithymia in Patients with Hidradenitis Suppurativa: A Cross-sectional Study - Amelia Głowaczewska; Jacek C. Szepietowski; Łukasz Matusiak (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)